A study of hematological parameters in patients with COVID-19 infection at a tertiary care centre - Patel, Keval Arvindbhai; Patel, Bimal; Parmar, Riddhi A; Sharma, Bhawana S; Thacker, Mansi; Patel, Navin (Journal of Pathology of Nepal, 2021)
Background: The corona virus disease 2019 is caused by the virus SARS-CoV-2 and is declared as a global pandemic by World Health Organization. Alterations in various hematological parameters have been recently documented in the world literature in SARS-Cov-2 infection. However, still there is paucity of hematological data in these patients. Hence this study is an attempt to evaluate the pattern of the hematological parameters in COVID-19 patients in the Indian population in our region. The objective of the study is to see the pattern of alteration in hematological parameters with emphasis on total leukocyte count, absolute lymphocyte count and platelet count in COVID 19 positive patients. Materials and Methods: This is an observational study in 50 patients with laboratory-confirmed COVID-19 status admitted to G.K. General Hospital & Gujarat Adani Institute of Medical Sciences, Bhuj, from 1st April 2020 to 30th June 2020. Statistical analysis of the data was carried out, and relevant findings were presented. Results: Among the 50 patients, there were 35 (70%) males and 15 (30%) females with an age range from 6 months to 82 years with twenty-five patients above 50 years. There was lymphopenia in 18 patients (36%), leukopenia in 2 patients (4%) and thrombocytopenia in 8 (16%) patients. Conclusions: Majority of the patients were elderly, and there was a male predominance. There was moderate to severe lymphopenia and mild thrombocytopenia.